Explaining reluctance to benefit from others' misfortune. (17th April 2018) - Lelieveld, Gert‐Jan; Inbar, Yoel; van Dijk, Eric
Abstract: The current article investigates decisions where people are not causing harm to others, but only benefit from the harm. Specifically, we assessed people's willingness to benefit from other's chance‐caused misfortunes. In 5 studies, examining real behavior of individuals in a television game show (Study 1) and using experimental betting tasks (Studies 2–5), we show that people are reluctant to benefit from the misfortunes of others. Although in all studies participants' decisions were objectively unrelated to the likelihood of misfortune befalling others, subsequent analyses indicate that people erroneously feel that benefitting from others' misfortune increases the likelihood that such harm will actually occur. The results are discussed in relation to the literature on moral decision‐making and magical thinking.